SISTEM PENGUKUR GSR, TEKANAN DARAH, DENYUT JANTUNG DAN SUHU TUBUH PADA MANUSIA - , USMAN ABD RAHMAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
GSR gauge system, Blood Pressure, Heart Rate and Body Temperature In Humans are digital electronics systems by addressing method ATmega32 Microcontroller IC with Programmable display the value of the condition of the body that serve as stress levels. Using the LCD as a display that would be classified under four stress conditions are relaxed, calm, anxious and tense. This gauge works based on the results of data processing information sent via GSR sensor, Blood Pressure, Heart Rate and Body Temperature. In this system the sensor readout method using the ADC (Analog to Digital Converter) and then processed by a microcontroller which has been programmed with the programming language C Code Vision AVR.